Baldwin, l’homotextualité et les identités plurielles : une rencontre à l’avant-garde - Jean-Paul Rocchi (Revue LISA)
Fifty years after Baldwin’s works were first published, they still disclose the essence of our dawning 21st century—the century of identity. Baldwin’s writing goes beyond the bare representation of racial and sexual categorisation. It launches a fierce attack upon the building-up of identities. Resisting self-erasure and self-negation, the author’s Black and gay consciousness frees itself from the traditional Western conceptions of spatio-temporality and distorts the conventional representation of masculinity-now seen through the lens of the sensuous trinity of the father, the son and the lover. Finally, it sheds a new light on Black identity, not only to be transmitted but also to be translated and transformed. Using psychoanalytical, sociological and semiological frames, this essay aims at showing how the process of writing in Baldwin’s fictional and non-fictional works inverts binarisms and dislocates the origin so as to oppose every attempt at defining identity. On the one hand, focusing more particularly on the interplay of identifications between the individual and the American community in Giovanni’s Room and on the other hand between the reader and the writer in “Notes of a Native Son”, this essay explores Baldwin’s major themes such as memory, homotextuality, the writer’s political philosophy, his ethics of inclusion and his position as an outsider. It also examines the Black and gay speech out of which springs his art of writing-in-beyond identity, in the political and literary vanguard.